Developing Nuclear Security Capacity of Indonesia’s Police and Security Officer: Lessons from Universitas Gadjah Mada’s Pilot Training - Susetyo Hario Putero Mr (International Journal of Nuclear Security, 2022)
Due to an increase in global nuclear security issues, there need to be improvements in human resources and security measures. The Republic of Indonesia is an archipelago country, which makes surveilling for nuclear security threats complicated. Recent radioactive material smuggling incidents proved that Indonesian police and security officers’ knowledge in nuclear security has been challenged and must be improved. In response, Universitas Gadjah Mada’s Nuclear Engineering Program composed a three-day pilot training program for local police and UGM's security officers in 2018. The objective of the training was to improve their capabilities in dealing with nuclear security issues around where they work and serve. Training materials were designed to introduce nuclear technology and provide the basic skills of handling nuclear security matters. The training was divided into 12 sessions, based on the needs stated by the Special Region of Yogyakarta's police chief. Lessons were delivered through traditional teaching, table-top exercises, exercises, and discussion. Fifteen-question pre-tests and post-tests were conducted to assess the officers’ knowledge of the training materials and the benefits of being trained. Based on the tests, we concluded that the participants’ understanding of nuclear security had improved. This increase in understanding was because the training materials fit their job needs, presented in various methods, and the participants’ awareness grew. It led to an increase in their awareness for securing the facilities utilizing radioactive sources in the Yogyakarta area. They said that the number of trainees in this event still does not meet the number of facilities that have to be secured. Therefore, the training should be carried out again and can be improved based on the participants' feedback. Furthermore, this training could be expanded and applied to the whole country.
Keywords: Indonesia; nuclear security; Universitas Gadjah Mada; capacity development